ARTIFICIAL INTELLIGENCE AND COPYRIGHT IN DIGITAL ART: LEGAL CHALLENGES FOR CONTEMPORARY VISUAL CULTURE - Sharma, Bhavana; Agarwala, Sumit; Sharma, Sangita; Dhoundiyal, Bhavana C.; Anuradha (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The development of Artificial Intelligence in a short period of time has had a crucial impact on the field of digital art, posing serious legal and ethical concerns as a part of the Copyright Law. This paper explores the AI-generated art and copyright, making a case of the issue of authorship, ownership, originality, and infringement in the modern visual culture. The study is multidisciplinary, incorporating legal analysis, comparative study and conceptual modeling to analyze the current copyright systems in major jurisdictions, such as the United States, European Union, United Kingdom and India. The results show that the existing copyright models are largely human centric and are poorly prepared to deal with the dynamics of AI-driven creativity. The confusion of the role of developers, users, and AI systems in the creative process makes attributing rights and responsibilities difficult. In addition, the fact that AI models are trained on copyrighted datasets poses infringement and fair use issues, and the international aspect of the digital platform exacerbates the inconsistency of regulations. The paper also examines how AI is affecting the wider visual culture, including how it is democratizing creativity, changing artistic activities, and thus redefining economic patterns within the creative sector. Nonetheless, it also highlights the issues of authenticity and artistic identity as well as ethical use of data. Through these reflections, this paper argues that adaptive law frameworks, models of hybrid authorship, and the globalization of copyright laws are necessary to handle the current situation in AI-generated art.